Fine control of nanoparticle sizes and size distributions: temperature and ligand effects on the digestive ripening process - Sahu, Puspanjali; Bhagavatula L. V. Prasad (Nanoscale, 2013)
It is demonstrated that a fine control over the size and size distribution of nanoparticles could be achieved using digestive ripening at different temperatures. Such variations in size and size distributions hugely influence the self-assembled processes in nanoparticles, and result in superlattice structures that are controlled by subtle interplay between ligand orientational entropy and their interdigitation and the van der Waals attraction between the metal cores.